Development of Interactive Learning Media to Improve Reading Comprehension Among Fourth Grade Elementary School Students - Riska Mahdalena; Deni Herdianto (AL-ISHLAH: Jurnal Pendidikan, 2026)
Reading comprehension is a fundamental skill in elementary education; however, many students experience difficulties due to limited engagement and the continued use of conventional teaching methods. This study aims to develop interactive learning media to enhance fourth-grade students’ reading comprehension in Indonesian language learning. This study employed a Research and Development (RD) design using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The sample consisted of 68 elementary school students. Data were collected through learning outcome tests, questionnaires, interviews, and observations. Instruments included validation sheets for material and media experts, as well as student and teacher response questionnaires. Data were analyzed to assess feasibility, practicality, and effectiveness, including a paired sample t-test to measure learning improvement.  The developed interactive media was rated highly feasible by material experts (87%) and media experts (95%). Practicality evaluations showed very positive responses from students (91%) and teachers (93%). Effectiveness testing revealed a significant improvement in students’ reading comprehension, with paired sample t-test results indicating p = 0.000 (p 0.05), confirming a statistically significant difference between pre-test and post-test scores.  The findings indicate that interactive learning media are feasible, practical, and effective in improving reading comprehension. The integration of multimedia elements enhances student engagement and supports active learning. Therefore, interactive media can serve as an effective instructional tool to improve literacy outcomes in elementary education, although further studies with broader samples are recommended.